Proinflammatory cytokines suppress nonsense-mediated RNA decay to impair regulated transcript isoform processing in pancreatic β cells - Ghiasi, Seyed M.; Marchetti, Piero; Piemonti, Lorenzo; Nielsen, Jens H.; Porse, Bo T.; Mandrup-Poulsen, Thomas; Rutter, Guy A. (Frontiers in Endocrinology, 2024)
Proinflammatory cytokines are implicated in pancreatic β-cell failure in type 1 and type 2 diabetes and are known to stimulate alternative RNA splicing and the expression of Nonsense-Mediated RNA Decay (NMD) components. Here, we investigate whether cytokines regulate NMD activity and identify transcript isoforms targeted in β-cells. A luciferase-based NMD reporter transiently expressed in rat INS1(832/13), human-derived EndoC-βH3 or dispersed human islet cells is used to examine the effect of proinflammatory cytokines (Cyt) on NMD activity. Gain-or loss-of function of two key NMD components UPF3B and UPF2 is used to reveal the effect of cytokines on cell viability and function.RNA-sequencing and siRNA-mediated silencing are deployed using standard techniques. Cyt attenuate NMD activity in insulin-producing cell lines and primary human β-cells. These effects are found to involve ER stress and are associated with downregulation of UPF3B. Increases or decreases in NMD activity achieved by UPF3B overexpression (OE) or UPF2 silencing, raises or lowers Cyt-induced cell death, respectively, in EndoC-βH3 cells, and are associated with decreased or increased insulin content, respectively. No effects of these manipulations are observed on glucose-stimulated insulin secretion.Transcriptomic analysis reveals that Cyt increase alternative splicing (AS)-induced exon skipping in the transcript isoforms, and this is potentiated by UPF2 silencing. Gene enrichment analysis identifies transcripts regulated by UPF2 silencing whose proteins are localized and/or functional in extracellular matrix (ECM) including the serine protease inhibitor SERPINA1/-1-antitrypsin, whose silencing sensitises β-cells to Cyt cytotoxicity. Cytokines suppress NMD activity via UPR signalling, potentially serving as a protective response against Cyt-induced NMD component expression. Our findings highlight the central importance of RNA turnover in -cell responses to inflammatory stress.